Association of IL23R Variants With Crohn's Disease in Korean Children - Jeana Hong; Jeana Hong; Hye Ran Yang; Hye Ran Yang; Jin Soo Moon; Ju Young Chang; Ju Young Chang; Jae Sung Ko (Frontiers Media S.A., 2019)
Background: The interleukin 23 receptor gene (IL23R) is strongly associated with Crohn's disease (CD). It is unknown whether genetic variations in IL23R determine susceptibility for pediatric CD in Asian populations. Here, we investigated the association between IL23R variants and CD in Korean children.Methods: Four single nucleotide polymorphisms (SNPs) of IL23R [rs76418789 (G149R), rs1004819, rs7517847, and rs1495965] were genotyped in 141 children with CD and 150 controls using DNA direct sequencing. The risk allele and genotype frequencies were compared between patients and controls. The association between clinical phenotypes and genotypes of patients was also analyzed.Results: Two IL23R SNPs, rs76418789 (G149R), and rs1495965, were associated with CD in Korean pediatric patients as defense and risk loci, respectively. The odds ratio (OR) for rs76418789 (G149R) and rs1495965 was 0.409 (95% confidence interval [CI], 0.177-0.944; p = 0.031) and 1.484 (95% CI, 1.070-2.059; p = 0.018), respectively. Patients with the homozygous G allele of rs1495965 showed higher CD risk than those with other genotypes (GG vs. AA: OR, 2.256; 95% CI, 1.136-4.478; p = 0.019; GG vs. GA+AA: OR, 2.000; 95% CI, 1.175-3.404; p = 0.010). Additionally, they were more likely to have relatively invasive disease behavior of stenosis and/or penetration than simple inflammation (OR, 2.297; 95% CI, 1.065-4.950; p = 0.032).Conclusions: This is the first study reporting IL23R variants in Asian pediatric patients with CD. IL23R was significantly associated with Korean pediatric CD, and the rs1495965 may influence the clinical features of CD in Korean children.